Padrão de ocorrência da Chikungunya na cidade de Fortaleza, de 2014 a 2018 - Azevedo, Camila de Sousa Lins (2019)
INTRODUCTION: The Chikungunya virus (CHIKV) belongs to the genus Alphavirus of the Togaviridae family. Mainly transmitted by Aedes mosquitoes. . The name "chikungunya" is derived from the word Kimakonde, which means "to be twisted", and describes the curved form of patients with joint pain. Chikungunya in humans was first reported in 1770. However, the virus was not isolated until the 1950s in Tanzania. The first records of chikungunya in Brazil occurred in 2010 in travelers from India and Indonesia. In 2014 two distinct CHIKV genotypes were isolated in two Brazilian cities, one in Oiapoque and the other in Feira de Santana. The first indigenous cases of Fortaleza were recorded at the end of 2015 and soon dispersed throughout the city explosively and with death records. OBJECTIVE: To characterize the occurrence and spread of Chikungunya cases in the city of Fortaleza between 2014 and 2018, considering the moment of introduction of the virus endemic. METHODS: This is a retrospective descriptive cross-sectional study of reported and confirmed Chikungunya cases and deaths in the city of Fortaleza, Ceará. RESULTS: The first imported cases were identified in 2014. The first indigenous cases in 2015. In the other years, most were adults, female and with high school education. The most common clinical signs were fever, arthralgia, headache and myalgia. Hypertension and diabetes were the most common comorbidities. The 2014 and 2015 chikungunya cases were all laboratory confirmed. In the other years on average the laboratory confirmation was (15.6%) in 2016 and (19.7%) 2017. In 2016 there were 25 deaths from chikungunya, in 2017 there were 144 deaths and 1 in 2018. The death went in both sexes. Especially in people over 60 years. 54.1% had some comorbidity. It was possible to observe an excess of death in 2016 (1,417) and in 2017 (3,668). CONCLUSION: It can be concluded that chikungunya virus accompanied by susceptible population and presence of vector can cause large epidemics with explosive character even followed. Fever may not be reported at the time of consultation with a healthcare professional. The evolution to death is very important especially in the elderly.